Inferior parietal transcranial direct current stimulation with training improves cognition in anomic Alzheimer's disease and frontotemporal dementia. Issue 2 (24th March 2017) - Roncero, Carlos; Kniefel, Heike; Service, Erik; Thiel, Alexander; Probst, Stephan; Chertkow, Howard
Abstract: Introduction: We evaluated whether transcranial direct current stimulation (tDCS) can improve picture‐naming abilities in subjects with anomic Alzheimer or frontotemporal dementias. Methods: Using a double‐blind crossover design, 10 participants were trained on picture naming over a series of 10 sessions with either 30 minutes of anodal (2 mA) tDCS stimulation to the left inferior parieto‐temporal region (P3) or sham stimulation. We evaluated performance on a trained picture‐naming list, an equivalent untrained list, and additional neuropsychological tasks. Results: Participants improved significantly more receiving real stimulation rather than sham stimulation (40% vs. 19%, P < .01), lasting at least 2 weeks after stimulation. Furthermore, these participants showed a small increase for untrained picture‐naming items and digit span when they received real stimulation but a decrease when sham stimulation was received. Discussion: tDCS stimulation has promise as a treatment for anomia in demented individuals and the effect can generalize to unstudied items as well as other cognitive abilities.